The influence of the Pringle maneuver in laparoscopic hepatectomy: continuous monitor of hemodynamic change can predict the perioperatively physiological reservation - Chen, Yi-Chan; Lee, Min-Hsuan; Hsueh, Shan-Ni; Liu, Chien-Liang; Hui, Chung-Kun; Soong, Ruey-Shyang (Frontiers in Big Data, 2023)
Importance This is the first study to investigate the correlation between intra-operative hemodynamic changes and postoperative physiological status. Objective Design, settings, and participants Patients receiving laparoscopic hepatectomy were routinely monitored using FloTract for goal-directed fluid management. The Pringle maneuver was routinely performed during parenchymal dissection and the hemodynamic changes were prospectively recorded. We retrospectively analyzed the continuous hemodynamic data from FloTrac to compare with postoperative physiological outcomes. Exposure The Pringle maneuver during laparoscopic hepatectomy. Main outcome(s) and measure(s) Results Stroke volume variation that did not recover from the relief of the Pringle maneuver during the last application of Pringle maneuver predicted elevated postoperative MELD-Na scores. Conclusions and relevance The complexity of the hemodynamic data recorded by the FloTrac system during the Pringle Maneuver in laparoscopic hepatectomy can be effectively analyzed using the growth mixture modeling (GMM) method. The results can potentially predict the risk of short-term liver function deterioration.